2018
DOI: 10.1111/1753-0407.12851
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular, cancer and mortality events after bariatric surgery in people with and without pre‐existing diabetes: A nationwide study

Abstract: For patients with pre-existing diabetes, the risk of death, cardiovascular events, and cancer after bariatric surgery was higher than for those without diabetes, whose mortality risk after surgery remains 35% higher than that of the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Advancing the understanding of clinical efficacy of bariatric surgery has focused on short-and long-term outcomes of obesity-related comorbidities, including type 2 diabetes mellitus [4,[11][12][13], primary cardiovascular risk factors [14][15][16], cardiovascular events such as myocardial infarction and stroke [17][18][19], cancer [20,21], and allcause mortality [7,9,22]. Multiple association studies relating bariatric surgery and mortality outcomes have been reported, with wide variation in study design pertaining to the following: participant number; control cohorts; mean follow-up; procedure type; age at surgery; clinical end points (i.e., life expectancy and death rates for all cause and cause specific); and presence or absence of prevalent diabetes [3,6,[23][24][25][26][27][28][29][30][31][32][33][34][35]. Study type has been predominately retrospective in nature, with the Swedish Obesity Subjects (SOS) study prospectively studied [7,22].…”
Section: Discussionmentioning
confidence: 99%
“…Advancing the understanding of clinical efficacy of bariatric surgery has focused on short-and long-term outcomes of obesity-related comorbidities, including type 2 diabetes mellitus [4,[11][12][13], primary cardiovascular risk factors [14][15][16], cardiovascular events such as myocardial infarction and stroke [17][18][19], cancer [20,21], and allcause mortality [7,9,22]. Multiple association studies relating bariatric surgery and mortality outcomes have been reported, with wide variation in study design pertaining to the following: participant number; control cohorts; mean follow-up; procedure type; age at surgery; clinical end points (i.e., life expectancy and death rates for all cause and cause specific); and presence or absence of prevalent diabetes [3,6,[23][24][25][26][27][28][29][30][31][32][33][34][35]. Study type has been predominately retrospective in nature, with the Swedish Obesity Subjects (SOS) study prospectively studied [7,22].…”
Section: Discussionmentioning
confidence: 99%